Role of Neutrophils in Disease Pathogenesis 2017
DOI: 10.5772/67798
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neutrophils in Cystic Fibrosis Lung Disease

Abstract: Cystic fibrosis (CF) is a genetic syndrome caused by mutations in the CF Transmembrane Conductance Regulator (CFTR) gene. In CF patients, chief morbidity and mortality are due to pulmonary manifestations. CFTR lack/dysfunction brings an altered ion flux through the airway epithelium and ablation of mucociliary clearance, which in turn ensues in colonization and infection by opportunistic bacterial pathogens and subsequent neutrophil-dominated inflammation. This response eventually leads to the damage of the lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 142 publications
(146 reference statements)
0
7
0
Order By: Relevance
“…The main culprit for this effect is represented by proteases secreted by neutrophils themselves. Neutrophil elastase (NE) has several potential roles in disabling neutrophils including cleavage of opsonophagocytosis proteins, such as iC3b, complement receptor 1 (CR1) and C5a receptor, the chemokine receptor CXR1, and TIM3 receptor leading to decreased galectin 9/TIM3 interactions [30]. Overall, the loss of these proteins is responsible for suboptimal local neutrophil priming and bacterial clearance.…”
Section: The Inflammatory Response In Cf Airwaysmentioning
confidence: 99%
“…The main culprit for this effect is represented by proteases secreted by neutrophils themselves. Neutrophil elastase (NE) has several potential roles in disabling neutrophils including cleavage of opsonophagocytosis proteins, such as iC3b, complement receptor 1 (CR1) and C5a receptor, the chemokine receptor CXR1, and TIM3 receptor leading to decreased galectin 9/TIM3 interactions [30]. Overall, the loss of these proteins is responsible for suboptimal local neutrophil priming and bacterial clearance.…”
Section: The Inflammatory Response In Cf Airwaysmentioning
confidence: 99%
“…The uncontrolled release of these enzymes causes lung tissue damage and severe airway inflammation. We have shown that P. aeruginosa LPS-induced MPO levels can be reduced by treatment with the histone deacetylase (HDAC) inhibitor, suberoylanilide hydroxamic acid (SAHA), plausibly by restoring the trafficking of ΔF508-CFTR, suggesting that a functional CFTR is required to keep a tab on uncontrolled neutrophil activation [ 172 ]. Mechanistically, an absence or dysfunction of CFTR in neutrophils results in the deactivation of the guanosine triphosphate (GTP)-binding protein Rab27a, which causes impaired granule exocytosis [ 168 , 172 ].…”
Section: Autophagy-mediated Cftr and Immune Response Dysfunctionmentioning
confidence: 99%
“…We have shown that P. aeruginosa LPS-induced MPO levels can be reduced by treatment with the histone deacetylase (HDAC) inhibitor, suberoylanilide hydroxamic acid (SAHA), plausibly by restoring the trafficking of ΔF508-CFTR, suggesting that a functional CFTR is required to keep a tab on uncontrolled neutrophil activation [ 172 ]. Mechanistically, an absence or dysfunction of CFTR in neutrophils results in the deactivation of the guanosine triphosphate (GTP)-binding protein Rab27a, which causes impaired granule exocytosis [ 168 , 172 ]. Several studies now agree that the pharmacological inhibition of CFTR or the mutant ΔF508-CFTR is sufficient to cause deregulated neutrophil activation via the activation of the NFκB pathway, resulting in hyperinflammation [ 172 ].…”
Section: Autophagy-mediated Cftr and Immune Response Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these mediators produce an amplification of the inflammatory response due to generation of more neutrophils and their recruitment and activation. The end-stage disease is determined by damage to bronchial walls by neutrophil-derived reactive oxygen species (ROS) and proteases [5].…”
Section: Introductionmentioning
confidence: 99%